Kinematic and kinetic synergies of the lower extremities during the pull in olympic weightlifting - Kipp, K.; Redden, J.; Sabick, M.; Harris, C. (Journal of Applied Biomechanics, 2012)
The purpose of this study was to identify multijoint lower extremity kinematic and kinetic synergies in weightlifting and compare these synergies between joints and across different external loads. Subjects completed sets of the clean exercise at loads equal to 65, 75, and 85% of their estimated 1-RM. Functional data analysis was used to extract principal component functions (PCF`s) for hip, knee, and ankle joint angles and moments of force during the pull phase of the clean at all loads. The PCF scores were then compared between joints and across loads to determine how much of each PCF was present at each joint and how it differed across loads. The analyses extracted two kinematic and four kinetic PCF`s. The statistical comparisons indicated that all kinematic and two of the four kinetic PCF`s did not differ across load, but scaled according to joint function. The PCF`s captured a set of joint- and load-specific synergies that quantified biomechanical function of the lower extremity during Olympic weightlifting and revealed important technical characteristics that should be considered in sports training and future research.